The predictive value of a preoperative systemic immune‐inflammation index and prognostic nutritional index in patients with esophageal squamous cell carcinoma. Issue 2 (2nd August 2018) - Zhang, Hongdian; Shang, Xiaobin; Ren, Peng; Gong, Lei; Ahmed, Ashique; Ma, Zhao; Ma, Rong; Wu, Xianxian; Xiao, Xiangming; Jiang, Hongjing; Tang, Peng; Yu, Zhentao
Abstract : Growing evidence indicates that systemic inflammation response and malnutrition status are correlated with survival in certain types of solid tumors. The aim of this study is to evaluate the association between the systemic immune‐inflammation index (SII) and prognostic nutritional index (PNI) and overall survival (OS) in patients with esophageal squamous cell carcinoma (ESCC) after esophagectomy. A consecutive series of 655 patients with resected ESCC who underwent esophagectomy were enrolled in the retrospective study. The preoperative SII was defined as platelet × neutrophil/lymphocyte counts. The PNI was calculated as albumin concentration (g/L) + 5 × total lymphocyte count (10 9 /L). The optimal cut‐off values of SII, neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and PNI were determined by receiver operating characteristic analysis. Survival analysis was performed using the Kaplan–Meier method with a log‐rank test, followed by a multivariate Cox proportional hazards model. A high SII was significantly related to tumor size, histological type, invasion depth, and TNM stage ( p  < 0.05). A low PNI was significantly associated with age, tumor size, invasion depth, lymph node metastasis, and TNM stage ( p  < 0.05). Univariate analysis revealed that age, smoking history, tumor size, invasion depth, lymph node metastasis, SII, NLR, PLR, and PNI were predictors of OS ( p  < 0.05). Multivariate analysis identified age ( p  = 0.041), tumor size ( p  = 0.016), invasion depth ( p  < 0.001), lymph node metastasis ( p  < 0.001), SII ( p  = 0.033), and PNI ( p  = 0.022) as independent prognostic factors correlated with OS. There was a significant inverse relationship between the SII and PNI ( r  = 0.309; p  < 0.001). The predictive value increased when the SII and PNI were considered in combination. Our results demonstrate that the preoperative high SII and low PNI are powerful indicators of aggressive biology and poor prognosis for patients with ESCC. The combination of SII and PNI can enhance the accuracy of prognosis. Abstract : (a) The preoperative high systemic immune‐inflammation index (SII) and low prognostic nutritional index (PNI) are powerful indicators of aggressive biology and poor prognosis for patients with esophageal squamous cell carcinoma (ESCC). (b) Combination of SII and PNI (coSII–PNI) clearly classified ESCC patients into three independent groups before surgery. (c) The coSII–PNI can enhance the accuracy of prognosis.